Effect of Angiotensin Receptor-neprilysin Inhibitor on Acute Kidney Injury in Patients With Acute Decompensated Heart Failure - Gonghao Li; Yanli Zhao; Zhongxing Peng; Kun Liu; Delu Yin; Yunfeng Zhao (Cardiology Discovery)
Objective:. The risk of acute kidney injury (AKI) is high in patients with acute decompensated heart failure (ADHF). The aim of this study is to analyze the role of urinary neutrophil gelatinase-associated lipocalin (uNGAL) in diagnosing AKI in patients with ADHF and evaluate the therapeutic effect of angiotensin receptor-neprilysin inhibitor (ARNI) on AKI. Method:. Sixty patients with ADHF were enrolled at the First Affiliated Hospital of Kangda College of Nanjing Medical University from January 2020 to June 2021, and randomized into 2 groups (ARNI group: 30 patients treated with tablets of sacubitril valsartan sodium; and angiotensin-converting enzyme inhibitor (ACEI) group: 30 patients treated with benazepril). The uNGAL level was measured immediately after as well as 1, 2, 3, and 7 d after hospital admission. The serum creatinine (sCr) level and estimated glomerular filtration rate (eGFR) were measured immediately as well as 2 and 7 d after hospital admission. The urine volume, dose of loop diuretics, and duration of hospital stay (DoHS) were recorded. Result:. The most valuable diagnostic metric for AKI in patients with ADHF was the uNGAL level 1 d after hospital admission, which had a sensitivity of 0.94, specificity of 0.84, and optimal cutoff of 125.62 μg/L. In the presence of AKI, during the first 2 d, patients in the ARNI-AKI and ACEI-AKI groups showed an increase in the sCr level and a reduction in the eGFR level, but there was no significant difference between the 2 groups (P > 0.05). After 7 d of treatment, the sCr level decreased and the eGFR level increased in both groups, with a significantly greater changes being observed in the ARNI-AKI group than in the ACEI-AKI group (P < 0.05, respectively). In the absence of AKI, the difference in the sCr level and eGFR between the 2 groups was not significant. The DoHS ((11.25 ± 2.38) d vs. (14.11 ± 2.89) d), urinary microalbumin level ((22.95 ± 6.04) mg/L vs. (31.91 ± 2.18) mg/L), and daily dose of loop diuretics ((19.03 ± 3.04) mg/d vs. (23.62 ± 4.46) mg/d) were significantly lower in patients with AKI in the ARNI group than in the ACEI group (P < 0.05, respectively). Conclusion:. In patients with ADHF, uNGAL measurement enables the diagnosis of AKI earlier than that using the sCr level by 1 to 2 d. ARNI treatment reduced the sCr level, facilitated eGFR recovery, reduced the daily dose of loop diuretics, and decreased the DoHS compared with that in patients receive ACEI treatment.